Lipid A Mimetics Based on Unnatural Disaccharide Scaffold as Potent TLR4 Agonists for Prospective Immunotherapeutics and Adjuvants. Issue 35 (11th May 2022) - Strobl, Sebastian; Hofbauer, Karin; Heine, Holger; Zamyatina, Alla
Abstract: TLR4 is a key pattern recognition receptor that can sense pathogen‐ and danger‐ associated molecular patterns to activate the downstream signaling pathways which results in the upregulation of transcription factors and expression of interferons and cytokines to mediate protective pro‐inflammatory responses involved in immune defense. Bacterial lipid A is the primary TLR4 ligand with very complex, species‐specific, and barely predictable structure‐activity relationships. Given that therapeutic targeting of TLR4 is an emerging tool for management of a variety of human diseases, the development of novel TLR4 activating biomolecules other than lipid A is of vast importance. We report on design, chemical synthesis and immunobiology of novel glycan‐based lipid A‐mimicking molecules that can activate human and murine TLR4‐mediated signaling with picomolar affinity. Exploiting crystal structure ‐ based design we have created novel disaccharide lipid A mimetics (DLAMs) where the inherently flexible β(1→6)‐linked diglucosamine backbone of lipid A is exchanged with a conformationally restrained non‐reducing βGlcN(1↔1′)βGlcN scaffold. Excellent stereoselectivity in a challenging β, β ‐1, 1′ glycosylation was achieved by tuning the reactivities of donor and acceptor molecules using protective group manipulation strategy. Divergent streamlined synthesis of β, β‐1, 1′‐linked diglucosamine‐derived glycolipids entailing multiple long‐chain ( R )‐3‐ acyloxyacyl residues and up two three phosphate groups was developed. Specific 3D‐molecular shape and conformational rigidity of unnatural β, β ‐1, 1′‐linked diglucosamine combined with carefully optimized phosphorylation and acylation pattern ensured efficient induction of the TLR4‐mediated signaling in a species‐independent manner. Abstract : TLR4 activating lipid A mimetics with picomolar affinity were assembled on the basis of an unnatural synthetic β, β‐1, 1′‐linked diglucosamine scaffold. Excellent stereoselectivity in a challenging β, β‐1, 1′‐glycosylation was achieved by tuning the reactivities of donor and acceptor molecules using protective group manipulation strategy. Specific 3D‐molecular shape of βGlcN(1↔1′)βGlcN disaccharide was decisive for induction of pro‐inflammatory signaling by disaccharide lipid A mimetics ( ββ ‐DLAMs) based thereof. Potent immunostimulating potential was confirmed in human and murine immune cells rendering ββ ‐DLAMs promising vaccine adjuvant candidates.